Developing a digital nomads destination from the ground up - Getman, Natalya (2022)
The society we live in is becoming more mobile. New technologies enable people to work remotely from anywhere. More people abandon their settled lifestyles to become digital nomads. Digital nomads work remotely and travel the world simultaneously. Destinations could benefit from their arrivals. Destinations and market players are trying to attract digital nomads by designing special offers and new visa policies. This thesis is looking into digital nomads tourism and potential ways for its development. The specific focus of the thesis is to find a way to develop digital nomads tourism in a destination where it did not exist on a large scale before. The case study is based on the example of the Madeira islands where in 2021 by initiative of the local government the destination started targeting digital nomads from around the world. With the help of this example and conducting a qualitative research some interesting findings emerged. These findings have helped to build a strategy development model that could be later adopted and implemented by other destinations. More destinations could become digital nomads destinations through careful planning, understanding the target audience, creating communities and hiring community leaders, working alongside with experienced entrepreneurs and digital nomads, building infrastructures and communicating the value of digital nomads tourism to the locals. It is also important to consider sustainability while planning a digital nomads tourism development in a destination with the specifics to each destination individually. The present case study is using the example of a small remote island where sustainability is crucial.